Technological properties of beneficial bacteria from the dairy environment and development of a fermented milk with the beneficial strain Lactobacillus casei MRUV6. Issue 2 (13th May 2020) - Colombo, Monique; Todorov, Svetoslav D.; Carvalho, Antonio F.; Nero, Luís A.
Abstract: In this research paper we describe the technological properties of beneficial lactic acid bacteria (LAB) obtained from a dairy production chain and the development of a fermented milk produced with Lactobacillus casei MRUV6. Fifteen LAB isolates ( Lactobacillus sp., Pediococcus sp. and Weissela sp.) presented acidifying abilities (pH ranges from 0.73 to 2.11), were able to produce diacetyl (except by 5 isolates) and exopolysaccharides, and two were proteolytic. L. casei MRUV6 was selected for producing a fermented milk, stored up to 35 d at 4 and 10°C. Counts on MRS agar with added vancomycin (10 mg/l) and MRS agar with added bile salts (1.5% w/v) ranged from 9.7 to 9.9 log CFU/g, independently of the tested conditions, indicating stability and intestinal resistance of L. casei MRUV6, despite some significant differences ( P < 0.05). The study demonstrated the technological potential of a potential probiotic candidate strain, L. casei MRUV6, to be used as a starter culture in the dairy industry.